2015
DOI: 10.1016/j.jfluidstructs.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Transient response of a ship to an abrupt flooding accounting for the momentum flux

Abstract: Numerical non-linear time domain simulation method for damaged ship motions is presented. Floodwater motion modelling is based on the lumped mass method with a moving free surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…This method has the advantage of dealing with large deformation problems of free surface flow and fluid-structure interaction. In addition, Manderbacka et al [17] and Acanfora et al [18] presented a non-linear time domain simulation method for damaged ships. The flooding water motion is based on the lumped mass method with a moving free surface, and the ship's transient response to an abrupt flooding is simulated.…”
Section: Introductionmentioning
confidence: 99%
“…This method has the advantage of dealing with large deformation problems of free surface flow and fluid-structure interaction. In addition, Manderbacka et al [17] and Acanfora et al [18] presented a non-linear time domain simulation method for damaged ships. The flooding water motion is based on the lumped mass method with a moving free surface, and the ship's transient response to an abrupt flooding is simulated.…”
Section: Introductionmentioning
confidence: 99%
“…Through the comprehensive analysis of the above simulation results, it can be found that the transient response of a ship to an abrupt flooding is dangerous. A numerical non-linear time domain simulation based on the lumped mass method [11] and an enhanced smoothed particle hydrodynamics (SPH) model were developed to investigate the response of a damaged ship under the condition of transient flooding water [12][13][14][15]. These numerical simulation methods have been proven to provide convenience and reliability for flooding research.…”
Section: Introductionmentioning
confidence: 99%
“…Developing fast numerical simulation tools, capable of modelling water dynamics inside a compartment, is a state of the art challenge. Some of them are based on the lumped mass approach [14]; some of them are based on shallow water equations [15,16]. In [17,18], the so-called quasi-static approach was introduced as the coupling of the equations of motions of a flooded ship in waves with the floodwater, characterized by a flat free surface, moving in phase with the ship.…”
Section: Introductionmentioning
confidence: 99%